Cucurbit[8]uril (CB[8])‐Based Supramolecular Switches. Issue 2 (8th November 2018) - Pazos, Elena; Novo, Paula; Peinador, Carlos; Kaifer, Angel E.; García, Marcos D.
Abstract: The use of cucurbit[8]uril as a molecular host has emerged in the chemical literature as a reliable strategy for the creation of dynamic chemical systems, owing to its ability to form homo‐ and heteroternary complexes in aqueous media with appropriate molecular switches as guests. In this manner, CB[8]‐based supramolecular switches can be designed in a predictable and modular fashion, through the selection of appropriate guests able to condition the redox, photochemical, or pH‐triggered behavior of tailored multicomponent systems. Furthermore, CB[8] allows the implementation of dual/triple and linear/orthogonal stimuli‐dependent properties into these molecular devices by a careful selection of the guests. This versatility in their design gives these supramolecular switches great potential for the rational development of new materials, in which their function is not only determined by the custom‐made stimuli‐responsiveness, but also by the transient aggregation/disaggregation of homo‐ or heteromeric building blocks. Abstract : Switch that : The capability of cucurbit[8]uril as a molecular host to form homo‐ and heteroternary complexes in aqueous media has fueled its use in supramolecular switches. The use of those dynamic systems is especially interesting since they can be reversibly transformed by the application of external stimuli, such as light, redox potential, or pH, and even allow the implementation of orthogonal stimuli responsiveness.